Web-Based Application Development using PHP-Native Framework on Agent of Change Integrity Zone Information System - Perdana, Adidtya; Farhana, Nurul Ain; Harliana, Putri; Karo Karo, Ichwanul Muslim (Sinkron : jurnal dan penelitian teknik informatika, 2024)
An Integrity Zone is an activity related to government policies and efforts to create an environment free from corruption, collusion, and nepotism (KKN). The Integrity Zone aims to encourage transparency, accountability, and clean practices in the management of a bureaucracy. To further the success of this Integrity Zone, a Agent of Change was formed who acts as a Role Model for all parties. As a role model, agents of change must be able to provide examples in attitude, behavior, and thinking. In addition, they must be able to provide creative solutions in dealing with problems in their agencies. And must be able to provide creative ideas to improve the performance of all parties. Sometimes, their ideas are not well documented. So a digital-based system is needed that can facilitate the work of these agents of change. For this reason, it is necessary to create a Web-based application for recording, reporting, and implementing change agent performance so that it is more optimal, efficient, and effective. In this study, the development of web-based applications using a framework with PHP-Native technology. Most PHP frameworks that exist today, use MVC and OOP technology but no one has utilized PHP-Native technology as a framework. This aims to facilitate the creation of applications for programmers who have not familiar with MVC or OOP concept.